SISTEM INFORMASI MONEV PENGENDALI JENTIK NYAMUK BERBASIS ANDROID MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT STUDI KASUS DI UOBF PUSKESMAS NGEMPIT - sigit riyadi (LPPM ITB Yadika Pasuruan, 2023)
Abstract: Jumantik or Lartic Monitoring Interpreter is the person in charge of carrying out inspection and monitoring of mosquito larvae, especially Aedes Aegypti and Aedes mosquitoes Aedes albopicus. These mosquitoes have a well-known health impact as Dengue Hemorrhagic Fever. P Health Center is one of the health agencies located in the area of Pasuruan Regency which has responsibility in providing health services to the community. This program The aim is that jumantik cadres can monitor mosquito larvae in places public facilities in the working area of the puskesmas are cramped so that the location can be more awake and clean so that it can reduce the growth rate of mosquito larvae. The system used by the school still uses sheets of paper containing forms Screening and monitoring. To assist in conducting monitoring and evaluation mosquito larvae, then a monitoring information system was made with android technology. The method used is the RAD (Rapid Application Development) method. Method Rapid Application Development is implemented on the system to be built. With this application with Android technology, it is hoped that it will make work easier Jumantik Cadres and Program Holders in monitoring places public facilities in the working area of the puskesmas are cramped.